2021
DOI: 10.3390/ani11030796
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Behaviours of Primitive Horses Based on Konik: A Preliminary Study

Abstract: This study aimed at assessing the behaviour of Konik geldings and mares, kept in a stable and in a free-range system, during behavioural tests regarded as a determinant of the exploration urge. A total of 19 Konik horses kept in individual stables and in a free-range system were included in the study. The experiment was conducted in five phases separated by five-day breaks. A one-stage passive human test was performed during the first phase, a three-stage active human test—2nd phase, a three-stage unknown obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…It was found that the filly most often showed exploratory behavior, it accounted for 54% of the time during the observation period. This form of behavior is innate, manifests itself at different stages of ontogenesis and provides a biologically adequate orientation of the behavior of animals in a situation of novelty (Jastrzębska 2021). A high level of research activity allows young animals to develop and gain personal experience, receiving vital information, thereby ensuring the adaptation of the organism to a dynamic external environment, and ultimately being one of the survival mechanisms of the individual and the species as a whole (Ivanov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the filly most often showed exploratory behavior, it accounted for 54% of the time during the observation period. This form of behavior is innate, manifests itself at different stages of ontogenesis and provides a biologically adequate orientation of the behavior of animals in a situation of novelty (Jastrzębska 2021). A high level of research activity allows young animals to develop and gain personal experience, receiving vital information, thereby ensuring the adaptation of the organism to a dynamic external environment, and ultimately being one of the survival mechanisms of the individual and the species as a whole (Ivanov et al 2013).…”
Section: Discussionmentioning
confidence: 99%